Surface treating agent for electronic-grade glass fiber cloth and preparation method of surface treating agent
By using a modifier and a special dispersant, a surface treatment agent for electronic grade fiberglass cloth was prepared, which solved the problems of poor water resistance, heat resistance and binding strength, and significantly improved its performance in copper clad production.
Patent Information
- Application Number
- CN202411928191.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the prior art, the water resistance, heat resistance and bonding power with resin of the electronic grade fiberglass cloth are not good, making it difficult to meet the requirements of copper clad production.
A surface treatment agent for electronic grade fiberglass cloth was prepared by mixing the modifier 10-(meth)acryloyloxydecylphosphate and a dispersant prepared by mixing sodium 3-chloro-2-hydroxypropane sulfonate with butyltriphenylphosphine bromide, combined with water and a cosolvent.
The water resistance, heat resistance and binding force with resin of the electronic grade fiberglass cloth are significantly improved, and its performance in copper clad fabric is improved.
Smart Images

Figure BDA0005209721470000051 
Figure BDA0005209721470000061
Abstract
Description
Technical Field
[0001] The invention relates to a surface treatment agent, in particular to a surface treatment agent for electronic grade glass fiber cloth and a preparation method thereof. Background Art
[0002] Electronic-grade glass fiber cloth is made from electronic-grade glass fiber yarn through warping, sizing, weaving, desizing, and chemical treatment. It is mainly used in the manufacture of copper-clad laminates, which are special basic materials for printed circuit boards (PCBs). Electronic-grade glass fiber cloth itself cannot be used directly for printing circuit boards. It needs to be combined with resin glue to make a semi-cured sheet, and then pressed with copper foil to make a copper-clad laminate, and finally used for printing circuit boards. However, pure glass fiber cloth is an inorganic fiber, while resin is an organic substance. The compatibility and bonding between the two are poor, so it is usually necessary to perform surface treatment on it. Although some surface treatment agents in the prior art can improve this, the surface treatment effect is general, and the water resistance and heat resistance of the treated electronic-grade glass fiber cloth are poor. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a surface treatment agent for electronic grade glass fiber cloth, which can effectively improve the water resistance and heat resistance of the electronic grade glass fiber cloth and the bonding strength between the electronic grade glass fiber cloth and the resin.
[0004] In order to solve the above technical problems, the technical solution of the present invention is:
[0005] A surface treatment agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 2-3 parts of a modifier, 4-5 parts of a dispersant, 6-9 parts of a cosolvent and 88-92 parts of water.
[0006] Furthermore, the modifier of the present invention is 10-(meth)acryloyloxydecyl phosphate.
[0007] Furthermore, the dispersant of the present invention is prepared by the following steps:
[0008] Sodium 3-chloro-2-hydroxypropane sulfonate is added to dimethyl sulfoxide and mixed evenly to obtain a solution A. Butyl triphenylphosphonium bromide is added to dimethyl sulfoxide and mixed evenly to obtain a solution B. The solution A and the solution B are mixed and magnetically stirred for 4-6 hours to obtain a mixed solution. The mixed solution is allowed to stand for 1-2 hours to separate into layers, and then the lower layer of liquid is taken out to obtain a dispersant.
[0009] Furthermore, in step (1) of the present invention, the ratio of sodium 3-chloro-2-hydroxypropane sulfonate to dimethyl sulfoxide in solution A is 0.6 mol:1L, the ratio of butyl triphenylphosphine bromide to dimethyl sulfoxide in solution B is 0.5 mol:1L, and the volume ratio of solution A to solution B is 1:1.
[0010] Furthermore, the co-solvent of the present invention is N,N-dimethylformamide.
[0011] Furthermore, the water described in the present invention is pure water.
[0012] Another technical problem to be solved by the present invention is to provide a method for preparing the surface treatment agent for electronic grade glass fiber cloth.
[0013] To solve the above technical problems, the technical solution is:
[0014] A method for preparing a surface treatment agent for electronic grade glass fiber cloth comprises the following steps:
[0015] S1 weighed the raw materials in parts by weight, the modifier, solvent was added to 1 / 4 weight of water, stirred for 20-30 minutes to obtain a mixed solution;
[0016] S2. The dispersant was added to the remaining water and stirred for 10-20 minutes to obtain a mixed solution II;
[0017] S3. Mix the mixed solution 1 obtained in step S1 and the mixed solution 2 obtained in step S2, and stir for 30-40 minutes to obtain a surface treatment agent for electronic grade glass fiber cloth.
[0018] Furthermore, in step S1 of the present invention, the stirring speed is 300 rpm.
[0019] Furthermore, in step S2 of the present invention, the stirring speed is 100 rpm.
[0020] Furthermore, in step S3 of the present invention, the stirring speed is 200 rpm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The modifier used in the present invention, 10-(meth)acryloyloxydecyl phosphate, can improve the compatibility between the electronic-grade glass fiber cloth and the resin, enhance the bonding force between the electronic-grade glass fiber cloth and the resin, and can also reduce the water absorption rate of the electronic-grade glass fiber cloth and improve the water resistance of the electronic-grade glass fiber cloth.
[0023] (2) The present invention also uses a dispersant prepared by a mixed reaction of sodium 3-chloro-2-hydroxypropane sulfonate and butyltriphenylphosphonium bromide, which can improve the coating uniformity of the surface treatment agent on the electronic-grade glass fiber cloth, thereby improving the heat resistance of the electronic-grade fiber cloth, and further improving the bonding strength between the electronic-grade glass fiber cloth and the resin. DETAILED DESCRIPTION
[0024] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention but are not intended to limit the present invention.
[0025] Example 1
[0026] The surface treatment agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 2.5 parts of 10-(methyl)acryloyloxydecyl phosphate, 4.5 parts of dispersant, 8 parts of N,N-dimethylformamide and 90 parts of pure water.
[0027] Wherein, the dispersant is prepared by the following steps:
[0028] Sodium 3-chloro-2-hydroxypropane sulfonate was added to dimethyl sulfoxide at a ratio of 0.6 mol:1 L and mixed evenly to obtain solution A. Butyl triphenylphosphonium bromide was added to dimethyl sulfoxide at a ratio of 0.5 mol:1 L and mixed evenly to obtain solution B. Solution A and solution B in a volume ratio of 1:1 were mixed and magnetically stirred for 5 hours to obtain a mixed solution. The mixed solution was allowed to stand for 1.5 hours to separate the layers and then the lower layer of liquid was taken out to obtain a dispersant.
[0029] The preparation method of Example 1 comprises the following steps:
[0030] S1 weighed the raw materials in parts by weight, 10- (meth) acryloyloxydecyl phosphate, N, N- dimethylformamide was added to 1 / 4 weight of pure water, stirred at 300 rpm for 25 minutes to obtain a mixed solution;
[0031] S2. The dispersant was added to the remaining pure water and stirred at 100 rpm for 15 minutes to obtain a mixed solution II;
[0032] S3. Mix the mixed solution 1 obtained in step S1 and the mixed solution 2 obtained in step S2, and stir at 200 rpm for 35 minutes to obtain a surface treatment agent for electronic grade glass fiber cloth.
[0033] Example 2
[0034] The surface treatment agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 2 parts of 10-(methyl)acryloyloxydecyl phosphate, 4 parts of dispersant, 6 parts of N,N-dimethylformamide, and 88 parts of pure water.
[0035] Wherein, the dispersant is prepared by the following steps:
[0036] Sodium 3-chloro-2-hydroxypropane sulfonate was added to dimethyl sulfoxide at a ratio of 0.6 mol:1 L and mixed evenly to obtain solution A. Butyl triphenylphosphonium bromide was added to dimethyl sulfoxide at a ratio of 0.5 mol:1 L and mixed evenly to obtain solution B. Solution A and solution B were mixed in a volume ratio of 1:1, and then magnetically stirred for 4 hours to obtain a mixed solution. The mixed solution was allowed to stand for 1 hour to separate into layers, and then the lower layer of liquid was taken out to obtain a dispersant.
[0037] The preparation method of Example 2 comprises the following steps:
[0038] S1 weighed the raw materials in parts by weight, 10- (meth) acryloyloxydecyl phosphate, N, N- dimethylformamide was added to 1 / 4 weight of pure water, stirred at 300 rpm for 20 minutes to obtain a mixed solution;
[0039] S2. The dispersant was added to the remaining pure water and stirred at 100 rpm for 10 minutes to obtain a mixed solution II;
[0040] S3. Mix the mixed solution 1 obtained in step S1 and the mixed solution 2 obtained in step S2, and stir at 200 rpm for 30 minutes to obtain a surface treatment agent for electronic grade glass fiber cloth.
[0041] Example 3
[0042] The surface treatment agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 2.5 parts of 10-(methyl)acryloyloxydecyl phosphate, 4 parts of dispersant, 7 parts of N,N-dimethylformamide and 91 parts of pure water.
[0043] Wherein, the dispersant is prepared by the following steps:
[0044] Sodium 3-chloro-2-hydroxypropane sulfonate was added to dimethyl sulfoxide at a ratio of 0.6 mol:1 L and mixed evenly to obtain solution A. Butyl triphenylphosphonium bromide was added to dimethyl sulfoxide at a ratio of 0.5 mol:1 L and mixed evenly to obtain solution B. Solution A and solution B in a volume ratio of 1:1 were mixed and magnetically stirred for 4.5 hours to obtain a mixed solution. The mixed solution was allowed to stand for 2 hours to separate the layers and then the lower layer of liquid was taken out to obtain a dispersant.
[0045] The preparation method of Example 3 comprises the following steps:
[0046] S1 weighed the raw materials in parts by weight, 10- (meth) acryloyloxydecyl phosphate, N, N- dimethylformamide was added to 1 / 4 weight of pure water, stirred at 300 rpm for 24 minutes to obtain a mixed solution;
[0047] S2. The dispersant was added to the remaining pure water and stirred at 100 rpm for 18 minutes to obtain a mixed solution II;
[0048] S3. Mix the mixed solution 1 obtained in step S1 and the mixed solution 2 obtained in step S2, and stir at 200 rpm for 32 minutes to obtain a surface treatment agent for electronic grade glass fiber cloth.
[0049] Example 4
[0050] The surface treatment agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 3 parts of 10-(methyl)acryloyloxydecyl phosphate, 5 parts of dispersant, 9 parts of N,N-dimethylformamide and 92 parts of pure water.
[0051] Wherein, the dispersant is prepared by the following steps:
[0052] Sodium 3-chloro-2-hydroxypropane sulfonate was added to dimethyl sulfoxide at a ratio of 0.6 mol:1 L and mixed evenly to obtain solution A. Butyl triphenylphosphonium bromide was added to dimethyl sulfoxide at a ratio of 0.5 mol:1 L and mixed evenly to obtain solution B. Solution A and solution B in a volume ratio of 1:1 were mixed and magnetically stirred for 6 hours to obtain a mixed solution. The mixed solution was allowed to stand for 2 hours to separate into layers, and then the lower layer of liquid was taken out to obtain a dispersant.
[0053] The preparation method of Example 4 comprises the following steps:
[0054] S1 weighed the raw materials in parts by weight, 10- (meth) acryloyloxydecyl phosphate, N, N- dimethylformamide was added to 1 / 4 weight of pure water, stirred at 300 rpm for 30 minutes to obtain a mixed solution;
[0055] S2. The dispersant was added to the remaining pure water and stirred at 100 rpm for 20 minutes to obtain a mixed solution II;
[0056] S3. Mix the mixed solution 1 obtained in step S1 and the mixed solution 2 obtained in step S2, and stir at 200 rpm for 40 minutes to obtain a surface treatment agent for electronic grade glass fiber cloth.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that the raw materials do not include 10-(meth)acryloyloxydecyl phosphate.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that the raw materials do not include a dispersant, and the step of preparing the dispersant is omitted.
[0061] Experimental example:
[0062] The E-grade electronic-grade glass fiber cloth was desized and immersed in the surface treatment agent (Example 1-4, Comparative Example 1-2), and dried at 80° C. to obtain the pretreated electronic-grade glass fiber cloth.
[0063] In parts by weight, 75 parts of epoxy resin E-44, 2.5 parts of dicyandiamide, 0.1 parts of dimethylimidazole, 28 parts of talc, and 70 parts of N,N-dimethylformamide were mixed and stirred evenly to obtain a resin adhesive solution. The pretreated electronic grade glass fiber cloth was immersed in the resin adhesive solution and dried at 130°C for 15 minutes to obtain a semi-cured sheet with an average thickness of 50 μm.
[0064] Four prepregs were stacked, and copper foil with a thickness of 18 μm was covered on the upper and lower sides respectively. The laminate was placed in a hot press and hot-pressed at a pressure of 2 MPa and 200° C. for 2 hours to obtain a copper-clad laminate with a thickness of 0.2 mm.
[0065] Test example 1:
[0066] The semi-cured sheets prepared in the experimental examples (Examples 1-4, Comparative Examples 1-2) were drilled with a blind hole having a bottom diameter of 60 μm and a top diameter of 70 μm using a laser drilling machine. The energy during drilling was 2 mJ, the pulse width was 4 μs, and the number of irradiations was 3 times. After the blind hole was decontaminated, it was observed with a scanning electron microscope to measure the maximum value Lm of the residual length of the glass fiber on the side wall of the blind hole in the horizontal direction. The smaller Lm is, the better the bonding force between the electronic grade glass fiber and the resin. The test results are shown in Table 1:
[0067] Lm(μm) Example 1 4 Example 2 6 Example 3 3 Example 4 5 Comparative Example 1 11 Comparative Example 2 9
[0068] Table 1
[0069] As can be seen from Table 1, the Lm of Examples 1-4 of the present invention are all small, indicating that the present invention can effectively improve the bonding strength between the electronic grade glass fiber cloth and the resin. Some of the raw materials and preparation steps used in Comparative Examples 1 and 2 are different from those in Example 1. Compared with Example 1, the Lm of Comparative Examples 1 and 2 are increased, indicating that the 10-(meth)acryloyloxydecyl phosphate and dispersant used in the present invention can effectively improve the bonding strength between the electronic grade glass fiber cloth and the resin.
[0070] Test Example 2:
[0071] Referring to the water absorption rate of the copper clad laminate (Examples 1-4, Comparative Example 1) prepared in the IPC-TM-6502.6 standard test experiment example, the lower the water absorption rate, the better the water resistance. The test results are shown in Table 2:
[0072]
[0073]
[0074] Table 2
[0075] As can be seen from Table 2, the water absorption rates of Examples 1-4 of the present invention are all low, indicating that the present invention can effectively improve the water resistance of electronic-grade glass fiber cloth and copper-clad laminate. Some of the raw materials used in Comparative Example 1 are different from those in Example 1. Compared with Example 1, the water absorption rate of Comparative Example 1 is significantly increased, indicating that the 10-(meth)acryloyloxydecyl phosphate used in the present invention can effectively improve the water resistance of electronic-grade glass fiber cloth and copper-clad laminate.
[0076] Test Example 3:
[0077] Referring to the glass transition temperature of the copper clad laminate (Examples 1-4, Comparative Example 2) prepared in the test example of GB / T 36800.12018 plastic thermomechanical analysis (TMA), the higher the glass transition temperature, the better the heat resistance. The test results are shown in Table 3:
[0078] Glass transition temperature(℃) Example 1 175 Example 2 172 Example 3 177 Example 4 174 Comparative Example 2 161
[0079] Table 3
[0080] As can be seen from Table 3, the glass transition temperatures of Examples 1-4 of the present invention are all relatively high, indicating that the present invention can effectively improve the heat resistance of electronic-grade glass fiber cloth and copper-clad laminate. Some of the raw materials and preparation steps used in Comparative Example 2 are different from those in Example 1. Compared with Example 1, the glass transition temperature of Comparative Example 2 is significantly reduced, indicating that the dispersant used in the present invention can effectively improve the heat resistance of electronic-grade glass fiber cloth and copper-clad laminate.
[0081] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A surface treatment agent for electronic grade glass fiber cloth, characterized in that: The invention is prepared from the following raw materials in parts by weight: 2-3 parts of a modifier, 4-5 parts of a dispersant, 6-9 parts of a co-solvent and 88-92 parts of water.
2. The surface treatment agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The modifier is 10-(meth)acryloyloxydecyl phosphate.
3. The surface treatment agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The dispersant is prepared by the following steps: Sodium 3-chloro-2-hydroxypropane sulfonate is added to dimethyl sulfoxide and mixed evenly to obtain a solution A. Butyl triphenylphosphonium bromide is added to dimethyl sulfoxide and mixed evenly to obtain a solution B. The solution A and the solution B are mixed and magnetically stirred for 4-6 hours to obtain a mixed solution. The mixed solution is allowed to stand for 1-2 hours to separate into layers, and then the lower layer of liquid is taken out to obtain a dispersant.
4. The surface treatment agent for electronic grade glass fiber cloth according to claim 3, characterized in that: In the step (1), the ratio of sodium 3-chloro-2-hydroxypropane sulfonate to dimethyl sulfoxide in solution A is 0.6 mol:1 L, the ratio of butyl triphenylphosphine bromide to dimethyl sulfoxide in solution B is 0.5 mol:1 L, and the volume ratio of solution A to solution B is 1:
1.
5. The surface treatment agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The cosolvent is N,N-dimethylformamide.
6. The surface treatment agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The water is pure water.
7. The method for preparing a surface treatment agent for electronic grade glass fiber cloth according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1 weighed the raw materials in parts by weight, the modifier, solvent was added to 1 / 4 weight of water, stirred for 20-30 minutes to obtain a mixed solution; S2. The dispersant was added to the remaining water and stirred for 10-20 minutes to obtain a mixed solution II; S3. Mix the mixed solution 1 obtained in step S1 and the mixed solution 2 obtained in step S2, and stir for 30-40 minutes to obtain a surface treatment agent for electronic grade glass fiber cloth.
8. The method for preparing a surface treatment agent for electronic grade glass fiber cloth according to claim 7, characterized in that: In the step S1, the stirring speed is 300 rpm.
9. The method for preparing a surface treatment agent for electronic grade glass fiber cloth according to claim 7, characterized in that: In step S2, the stirring speed is 100 rpm.
10. The method for preparing a surface treatment agent for electronic grade glass fiber cloth according to claim 7, characterized in that: In step S3, the stirring speed is 200 rpm.
Citation Information
Patent Citations
Carbon-nanotube-containing glass fiber wetting agent, and preparation method and application thereof
CN104086094A
Electronic grade glass fiber cloth treating agent and glass fiber cloth manufactured by treating agent
CN109505125A
Ultra-thin electronic glass fiber cloth surface treatment fluid and preparation method thereof
CN111576040A
Electronic-grade glass cloth surface treating agent and preparation method thereof
CN116876216A
Electronic-grade glass fiber cloth surface treating agent and preparation method thereof
CN118374973A
Cited By
Glass fiber cloth treating agent, high-CAF-resistance glass fiber cloth and preparation method of high-CAF-resistance glass fiber cloth
CN119411394A
A glass fiber cloth treating agent, a glass fiber cloth with high CAF resistance, and a method for manufacturing the same
CN119411394B